1982
DOI: 10.1007/bf01262427
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure ofPeriplaneta americana neurons in long-term culture

Abstract: A new culture technique is described for dissociated ganglia of embryos of Periplaneta americana. Neurons obtained by the mechanical dissociation of ganglia from 23-26 day old embryos were grown for seven days in a combination of Schneider's Drosophila Medium and Eagle's Basal Medium and then transferred to a combination of Leibovitz's L-15 Medium and Yunker's Modified Grace's Medium supplemented with ecdysone. Neurons cultured in this way survived for periods in excess of one month. The cells had a typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…4). As both neurons and glial cells can be severely damaged during the culturing procedure, many of them die and disintegrate (Beadle et al, 1982(Beadle et al, , 1987; this study). Therefore viability testing is essential to distinguish HRP-negative glial cells from membraneless remnants of dead cells.…”
Section: Microscopy Research and Techniquementioning
confidence: 96%
See 2 more Smart Citations
“…4). As both neurons and glial cells can be severely damaged during the culturing procedure, many of them die and disintegrate (Beadle et al, 1982(Beadle et al, , 1987; this study). Therefore viability testing is essential to distinguish HRP-negative glial cells from membraneless remnants of dead cells.…”
Section: Microscopy Research and Techniquementioning
confidence: 96%
“…Nevertheless, the morphology of glial cells from adult cockroaches (Howes et al, 1989), pupal honeybees (Gascuel and Masson, 1991), and locust embryos ( Vanhems and Delbos, 1987) has been studied in vitro and a number of functional studies revealed that insect glial cells express high affinity transporters for L-glutamate, GABA, and histamine (Campos-Ortega, 1974;Borycz et al, 2002;Soustelle et al, 2002, Freeman et al, 2003, respond to neuronal transmitters (Giles and Usherwood, 1985;Leitch et al, 1993;Schofield and Treherne, 1985) and may require neuron-derived trophic signals for survival and differentiation (Bergmann et al, 2002;Hidalgo et al, 2001;Sen et al, 2004). A prerequisite for in vitro studies on primary cell cultures from insect nervous systems is the reliable distinction of glial and neuronal cell bodies, which is especially problematic in fresh cell cultures, where both cell types assume spherical shapes and lack characteristic processes (Beadle et al, 1982(Beadle et al, , 1987. A simple and widely used method to identify glial cells in histological studies is based on the absence of antihorseradish peroxidase (HRP) immunoreactivity, which labels the pan-neuronally expressed surface protein Nervana (Jan and Jan, 1982;Sun and Salvaterra, 1995a,b) and this method has recently been adopted to identify cultured glia cells (Loesel et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By following the method of Beadle et al (1982), APRs were fixed for 1 hour at 4°C in 2% gluteraldehyde (grade I, 25% aqueous; Sigma) in 0.1 M cacodylate buffer (pH 7.2). The interval between removal from the ganglion and fixation was 30 -60 minutes, depending on the number of cells to be processed.…”
Section: Preparation Of Aprs For Transmission Emmentioning
confidence: 99%
“…Since many years also insect neurons have been used in cell culture [2][3][4][5][6][7][8][9]. The cells in those cultures are often unidentified, thereby loosing the advantages of the identified neuron concept.…”
Section: Introductionmentioning
confidence: 99%